High-Risk Human Papillomavirus Is Associated with HIV Acquisition among South African Female Sex Workers. (24th July 2011) - Auvert, Bertran; Marais, Dianne; Lissouba, Pascale; Zarca, Kevin; Ramjee, Gita; Williamson, Anna-Lise
Abstract : Background . Mounting evidence suggests an association between human papillomavirus (HPV) and HIV acquisition. This study aimed to explore this association among South African female sex workers (FSWs). Methods . We used data from 88 HIV-negative FSWs who participated in a vaginal gel (COL-1492) trial. Cervicovaginal rinse samples, obtained before HIV-seroconversion, were genotyped into high-risk (HR-) and low-risk (LR-) HPV. HIV-adjusted hazard ratios (aHRs) and 95% confidence intervals (CI) were estimated using Cox survival analysis. Results . HR- and LR-HPV prevalences were 70.5% (95% CI : 60.5–79.2) and 60.2% (95% CI : 49.9–70.0), respectively. Twenty-five women HIV seroconverted. Controlling for background characteristics and other sexually transmitted infections, HIV aHR increased by a factor of 1.7 (95% CI : 1.01–2.7, P linear trend = 0.045) for an increase of one unit of the number of HR-HPV genotypes. Conclusions . HIV seroconversion among FSWs is associated with genital HR-HPV infection. Further investigation is warranted, including testing the possible protective effect of available HPV vaccines on HIV acquisition.